Eurynothrips Bagnall (Thysanoptera, Phlaeothripinae): a rare and long-lost Australian genus, with one new gall-inducing species - Mound, Laurence A.; Tree, Desley J. (Zootaxa, 2021)
The monotypic genus of horn-headed thrips, Eurynothrips Bagnall, had not been seen since its discovery in the early 1900’s in northern Australia, and nothing is known of its biology. A second species of the genus, E. laheyi sp.n., is described from southern Queensland, inducing galls on the young terminal leaves of the small tree, Planchonella pohlmaniana [Sapotaceae].